2015
DOI: 10.1111/cpr.12187
|View full text |Cite
|
Sign up to set email alerts
|

miR‐454 is down‐regulated in osteosarcomas and suppresses cell proliferation and invasion by directly targeting c‐Met

Abstract: Reduced-expression of miR-454 in osteosarcoma cells promoted tumour growth by targeting c-Met, thus miR-454 may be a potential therapy target for this tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 41 publications
1
55
0
Order By: Relevance
“…Osteosarcoma is the most prevalent malignant tumor of bone and is usually observed in young adults and adolescents [1][2][3][4][5]. Despite the recent advances in the treatment of osteosarcoma such as radiation therapy, adjuvant chemotherapy and surgery that have been achieved, the relative 5-year survival rate of osteosarcoma patients remains discontent [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma is the most prevalent malignant tumor of bone and is usually observed in young adults and adolescents [1][2][3][4][5]. Despite the recent advances in the treatment of osteosarcoma such as radiation therapy, adjuvant chemotherapy and surgery that have been achieved, the relative 5-year survival rate of osteosarcoma patients remains discontent [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies have showed that miRNAs play pivotal roles in cell proliferation, metabolism, differentiation, invasion and migration [1824]. More importantly, miRNAs play important roles in cancer progression and initiation and function as tumor suppressors or oncogenes [2527]. Abnormal expressions of miRNAs are associated with various cancers such as gastric cancer, renal cell carcinoma, breast cancer, ovarian carcinoma and osteosarcoma [2832].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 11 miRNAs have never been studied in liver cancer (Table III). Among the 11 differentially dysregulated miRNAs, the function of miR-374a, miR-188-5p, miR-1183, miR-454, miR-324-3p, miR-484, miR-3188, and miR-216b have been studied in human cancers (27,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43); however, the exact function of miR-4271, miR-1471 and miR-3610 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that miR-454 acts as an oncogene or tumor suppressor in cancer (39)(40)(41). miR-454 has been reported to be decreased in tissue of patients with esophageal cancer compared with normal tissue, which may perform as novel molecular markers of esophageal cancer (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation